Profile of High School Students Practicum Performance Ability on the Material Optics Using PhET Virtual Laboratory - Butar Butar, Debora Pebriany; Sunarti, Titin (Universitas Halu Oleo, 2021)
Physics is very closely related to finding out and understanding nature systematically, so that physics is not only the mastery of a collection of knowledge in the form of concepts but also a performance process. The purpose of this study was to describe the profile of student’s performance assessment abilities using the virtual PhET application. Previously carried out the development of performance assessment instruments and student worksheets using the 4-D model, namely the stages of defining, designing, developing, and disseminating. However, this research was only carried out until the develop stage. The research instrument was the validation instrument for student worksheets and the validation instrument for performance assessment. Research data includes data on the validity of student worksheet, validity of performance assessment instruments, and data on student performance abilities. The subjects of this study were 36 students of class XI MIPA 1 SMA Negeri 3 Sidoarjo. The validators of this study were two lecturers at the Department of Physics, Faculty of Mathematics and Natural Sciences, UNESA. Based on the research results obtained: 1) Student worksheets developed has a validity value of 89.79% with very valid criteria and the performance assessment instrument sheet developed has a validity value of 95.00% with very valid criteria 2) The performance profile of students in formulating problems, formulating hypotheses, identifying variables, designing experimental procedures, collecting data, analyzing data, and drawing conclusions stated to be very good with a value of 97.31% for the reflection experiment and 95.57% for the refraction experiment.